ETOS KERJA KEPALA MADRASAH MA TRI BHAKTI AT- TAQWA KEPAYANG LEMPUING OGAN KOMERING ILIR TAHUN PELAJARAN 2023/ 2024 - Iif Roikhatul Jannah (UNISAN JURNAL, 2024)
The supervision management of madrasah principals has an influence on improving the performance of certified teachers. This means that madrasa heads who are able to carry out their duties and responsibilities as supervisors well will further improve the performance of their teachers who have been certified. The results of the researcher’s pre-survey, although the head of MTs Negeri 1 Tanjungkarang has carried out his duties and responsibilities as a supervisor and 88.5% of Islamic Religious Education teachers have been certified, the performance of certified Islamic Religious Education teachers still needs to be improved. For this reason, researchers are interested in conducting further research on "The work ethic of the head of the MA Tri Bhakti At-Taqwa Kepayang Lempuing Ogan Komering Ilir madrasa for the 2023/2024 academic year" The formulation of the research problem is whether there is an influence of management supervision of madrasah heads on the performance of certified Islamic Religious Education teachers. The aim of the research is to determine the work ethic of the head of the MA Tri Bhakti At-Taqwa Kepayang Lempuing Ogan Komering Ilir madrasa for the 2023/2024 academic year. This research uses quantitative methods. The data collection technique used a questionnaire with research respondents of 23 certified Islamic Religious Education teachers. Data analysis uses simple correlation and regression techniques. The conclusion obtained is that there is a work ethic of the head of the MA Tri Bhakti At-Taqwa Kepayang Lempuing Ogan Komering Ilir madrasa for the 2023/2024 Academic Year. This conclusion is based on the finding that the strength of the influence of management supervision of the head of the madrasa on the performance of certified Islamic Religious Education teachers is 0.587 which is categorized as moderate and the r value is smaller than the level used (namely 0.003) or 0.000<0.003, meaning that there is a significant influence between the supervisory management of madrasah principals and the performance of certified teachers.